Knowledge Sharing, Budaya Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. Adam Dani Lestari - Sanny Synthia; Purnama Yanti Purba; Hendra Winarta; Iknasus Silaban (Journal of Management and Bussines (JOMB), 2023)
This research aims to test and analyze the influence of Knowledge Sharing, Work Culture and Work Environment on Employee Performance at PT. Adam Dani Lestari. The research method used was quantitative with the sampling technique being simple random sampling with a sample size of 105 employees. Partial research results: Knowledge Sharing has a positive and significant effect on employee performance, Work Culture has a positive and significant effect on employee performance, and the Work Environment has a positive and significant effect on employee performance at PT. Adam Dani Lestari. On top of that, at PT. Adam Dani Lestari, knowledge sharing, work culture, and environment all work together to positively and significantly affect employee performance. Conclusion: Research demonstrates a simultaneous and limited impact of the variables Knowledge Sharing, Work Culture, and Work Environment on employee performance. Keywords: Work Culture, Knowledge Sharing, Employee Performance, Work Environment